ANFIS Controller of PV Assisted Custom Power Device for Improving Power Quality - Mr. Kamaraja A. S., Dr. Rathina Prabha N. (International Journal of Advanced Science and Technology, 2020)
Power Quality (PQ) Enhancement using custom power devices namely, DVR which is connected to the array of Photo Voltaic (PV) cells can be done by means of a newcontrol algorithm Synchronous Reference Frame (SRF) modelthrough Adaptive Neuro-Fuzzy inference system (ANFIS) is suggestedfor the creation of reference DVR voltages. The proposed DC-DC boost converter and DVR are used to mitigate the sag/swell and harmonics due to the presence of non-linear power electronic loads. A voltage source inverter (VSI) where a capacitor is devoted to it to ensure reliable distribution the compensating reactive power. An ANFIS controller is proposed for analyzing PV. PQ enhancement is done using MATLAB/SIMULINK environment and the results are validated by other intellectual controllers, that is Fuzzy Logic controller (FLC) and ANFIS controller and it provides healthier harmonics compensation equated to the conventional controllers.